2012
DOI: 10.3109/09638288.2011.645111
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experience of post-stroke fatigue in community dwelling stroke survivors: a prospective qualitative study

Abstract: The results of this study suggest that in spite of reasonable objective physical recovery post-stroke, fatigue in community-dwelling stroke survivors may be disabling. The use of qualitative methodology was sensitive in identifying the factors that play a role in the experience of fatigue. The essential role of health professionals in this context is to provide support and education regarding fatigue and to promote participation after stroke in therapy programs. Routine practice for stroke services should incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
126
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(136 citation statements)
references
References 29 publications
9
126
0
1
Order By: Relevance
“…Hand pain and fatigue may also be caused by conditions such as carpal tunnel syndrome (Kuo et al, 2014) or writer's cramp (Hallett, 2006). Pain and fatigue are secondary consequences of conditions such as stroke (White et al, 2012), and these symptoms may have a cumulative negative impact on handwriting. Finally, upper limb injuries may affect handwriting performance due to weakness, pain or reduced range of motion.…”
Section: Conditions Which May Cause Reduced Handwriting Performance Imentioning
confidence: 99%
“…Hand pain and fatigue may also be caused by conditions such as carpal tunnel syndrome (Kuo et al, 2014) or writer's cramp (Hallett, 2006). Pain and fatigue are secondary consequences of conditions such as stroke (White et al, 2012), and these symptoms may have a cumulative negative impact on handwriting. Finally, upper limb injuries may affect handwriting performance due to weakness, pain or reduced range of motion.…”
Section: Conditions Which May Cause Reduced Handwriting Performance Imentioning
confidence: 99%
“…Furthermore, PSF has been found to have a negative effect on quality of life [2,10], rehabilitation outcomes [11], and even mortality [12][13][14]. However, PSF is often misdiagnosed [11,15,16] and evidence-based clinical guidelines for dealing with PSF are scarce [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A few qualitative studies in small focus groups have demonstrated that patients with PSF report a great need for information on the syndrome [15,16]. Patients reported that the lack of information led to confusion and distress, which in turn elongated the time needed to adjust to the fatigue [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations